A nitrogen-doped biomass-based porous carbon material and its preparation method and application
By doping nitrogen into biomass-based porous carbon materials, combined with ball milling and carbonization processes, nitrogen-doped biomass-based porous carbon materials with high specific surface area and uniform pore size distribution are prepared, solving the problem of insufficient adsorption capacity of existing materials. , achieving more efficient carbon dioxide capture.
Patent Information
- Application Number
- CN202411703339.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The surface area and pore size distribution of existing carbon dioxide adsorption materials is not uniform enough, resulting in insufficient adsorption capacity and cannot meet the market's demand for efficient carbon dioxide capture.
The nitrogen-doped biomass-based porous carbon material is prepared through ball milling and carbonization steps, and reasonable material ratios and process parameters are designed to improve the uniformity of the specific surface area and pore size distribution of the material.
It significantly improves the uniformity of the specific surface area and pore size distribution of the material, enhances the adsorption capacity of carbon dioxide, and has good application prospects and practical value.
Smart Images

Figure CN119191273B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon materials, and in particular, relates to a nitrogen-doped biomass-based porous carbon material and a preparation method and application thereof. Background Art
[0002] At present, in order to solve the serious impact of large amounts of carbon dioxide on the environment and climate, the research on carbon dioxide capture technology has received great attention. The key to carbon dioxide capture technology is to develop adsorbents with good adsorption effects. In recent years, some porous materials such as activated carbon, zeolite molecular sieves and metal organic framework materials have been studied and applied to carbon dioxide adsorption. Porous carbon materials have a large specific surface area and pore volume, which is conducive to the physical adsorption of CO2, and have become one of the ideal choices for carbon dioxide adsorption materials.
[0003] The inventor has previously conducted a series of studies on the development of carbon dioxide adsorption materials and nitrogen-containing porous carbon materials: For example, in CN201710364105.9, a mixed low eutectic salt composed of LiNO3, KNO3 and K2SO4 is added to the organic wet gel preparation step to obtain a microporous carbon aerogel with high specific surface area, narrow pore size distribution range, large pore volume, and strong adsorption capacity for carbon dioxide. CN201911004675.2 involves a preparation method and application of a nitrogen-containing porous carbon material based on polyaspartate, in which polyaspartate is placed in a carbonization furnace and carbonized under vacuum conditions to obtain a black nitrogen-containing carbon material, and then the nitrogen-containing porous carbon material is obtained by acid washing. The nitrogen-containing porous carbon material obtained by the provided method has a large specific surface area, and the distribution of nitrogen atoms and pore size is more uniform. The above method provides a reference for the preparation of carbon materials with large specific surface area, large pore volume, concentrated pore size distribution, and strong adsorption capacity.
[0004] As the market demand and requirements for carbon dioxide adsorbent materials continue to increase, it is of great significance to develop a carbon dioxide adsorbent material with high surface area, uniform pore size distribution and good adsorption performance. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a nitrogen-doped biomass-based porous carbon material and a preparation method and application thereof.
[0006] To solve the above problems, the technical solution adopted by the present invention is:
[0007] Technical topic 1:
[0008] A nitrogen-doped biomass-based porous carbon material, the preparation steps are as follows:
[0009] S1. Ball milling: placing the biomass raw material, the crosslinking agent, 2,2-azobis(2-methylpropylimidazole) dihydrochloride, ammonium persulfate, hexamethylenediamine, a mixture of montmorillonite and hydrotalcite, and distilled water in a high-energy ball mill for ball milling to obtain an intermediate product mixture, which is then dried to obtain a solid intermediate product;
[0010] S2, carbonization: carbonize the solid intermediate obtained in S1 under a protective gas atmosphere to obtain a black product;
[0011] S3, pickling: pickling the black product obtained in S2 to obtain a product carbon material;
[0012] The biomass raw material includes one or more of chitosan, glucosamine, chitosan oligosaccharide and hydroxypropyl chitosan;
[0013] The cross-linking agent includes one or more of geniposide, geniposide and geniposide.
[0014] As a further improvement of the present invention, the mass ratio of the biomass raw material, the crosslinking agent, 2,2-azobis(2-methylpropylimidazole) dihydrochloride, ammonium persulfate, hexamethylenediamine, a mixture of montmorillonite and hydrotalcite, and distilled water is 10:3-8:1-2:1-2:1-3:2-4:20-50.
[0015] As a further improvement of the present invention, the mass ratio of the biomass raw material, the crosslinking agent, 2,2-azobis(2-methylpropylimidazole) dihydrochloride, hexamethylenediamine, the mixture of montmorillonite and hydrotalcite, and distilled water is 10:5:1.5:1.5:2:3:30.
[0016] As a further improvement of the present invention, the mass ratio of montmorillonite to hydrotalcite in the mixture of montmorillonite and hydrotalcite is 1:0.4-2.7.
[0017] As a further improvement of the present invention, the ball milling operation is: ball milling mixing at a rotation speed of 80-150r / min for 30-60min, and then repeating the ball milling 3-5 times at a rotation speed of 500-800r / min, the single ball milling time is 20-40min, and standing for 30-60min in between.
[0018] As a further improvement of the present invention, the protective gas introduction rate is 10-30 mL / min; the protective gas includes one or more of nitrogen, argon and helium.
[0019] As a further improvement of the present invention, the carbonization operation is: heating from room temperature to 800-1000°C at a rate of 2-3°C / min, keeping the temperature for 2-4 hours, and then cooling to room temperature at a rate of 3-8°C / min.
[0020] As a further improvement of the present invention, the pickling operation is: washing the product with a hydrochloric acid solution, then rinsing with distilled water, and repeating the operations of pickling and then rinsing with water until the distilled water rinse is neutral.
[0021] Technical theme 2:
[0022] A method for preparing nitrogen-doped biomass-based porous carbon material as described in technical subject one.
[0023] Technical Theme 3:
[0024] An application of nitrogen-doped biomass-based porous carbon material in the field of CO2 adsorption as described in Technical Topic 1.
[0025] The beneficial effects of adopting the above technical solution are:
[0026] 1. The present invention enables the biomass raw material cross-linked material to have more porous structures, improves the content of microporous structures, increases the porosity and specific surface area of the cross-linked material, and makes the pore size distribution of the material prepared by the present invention more uniform and the surface area larger through the design of the added materials and the dosage and the exploration of process parameters.
[0027] 2. The present invention adopts a water solvent ball milling method. The ball milling raw material is a solid-liquid mixture. The addition of water during ball milling can make the raw materials mixed more evenly. During the high-speed ball milling process, the mechanical energy of the ball mill is converted into the chemical energy of the raw materials, promoting polymerization and cross-linking between the raw materials.
[0028] 3. The preparation method provided by the present invention has a simple process, is easy to operate, and has a thorough reaction. It also has a high reaction yield. In addition, the preparation process of the present invention does not produce any by-products that are harmful to the environment, thus meeting green environmental protection requirements.
[0029] 4. The nitrogen-doped biomass-based porous carbon material provided by the present invention has a high specific surface area and good carbon dioxide adsorption capacity, and has good application prospects and practical value. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a microscopic morphology of the nitrogen-doped biomass-based porous carbon material obtained in Example 1 of the present invention;
[0031] Figure 2 is a nitrogen adsorption-desorption curve diagram of the nitrogen-doped biomass-based porous carbon material obtained in Example 1 of the present invention;
[0032] Figure 3 is a CO2 adsorption curve of the nitrogen-doped biomass-based porous carbon material obtained in Example 1 of the present invention;
[0033] Figure 4 This is a pore size distribution diagram of the nitrogen-doped biomass-based porous carbon material obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the present invention clearer, the invention is clearly and completely described below in conjunction with specific embodiments, wherein the parts described in this embodiment are all parts by mass.
[0035] Example 1
[0036] A nitrogen-doped biomass-based porous carbon material, the preparation steps are as follows:
[0037] S1, ball milling: 10 parts of chitosan, 5 parts of geniposide acid, 1.5 parts of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, 1.5 parts of ammonium persulfate, 2 parts of hexamethylenediamine, 3 parts of a mixture of montmorillonite and hydrotalcite in a mass ratio of 1:1 and 30 parts of distilled water are placed in a high-energy ball mill, ball milled and mixed at a speed of 100 r / min for 45 min, and then the ball milling is repeated 4 times at a speed of 600 r / min, with a single ball milling time of 30 min, and the intermediate product mixture is allowed to stand for 45 min to obtain an intermediate product mixture, which is dried to obtain a solid intermediate product;
[0038] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0039] S3, pickling: The black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water rinse was neutral to obtain a nitrogen-doped biomass-based porous carbon material with a yield of 35%.
[0040] Microscopic analysis of the obtained nitrogen-doped biomass-based porous carbon material showed that Figure 1 As shown, it can be observed that there are abundant pore structures distributed on the surface of the material, which provides sufficient sites for CO2 adsorption;
[0041] The nitrogen-doped biomass-based porous carbon material was subjected to nitrogen adsorption and desorption tests. Figure 2 As shown, the specific surface area of the obtained carbon material is 936 cm 2 / g, pore size distribution is 3.8-5.5nm;
[0042] The obtained nitrogen-doped biomass-based porous carbon material was subjected to a CO2 adsorption test. The results are as follows: Figure 3 shown.
[0043] Example 2
[0044] A nitrogen-doped biomass-based porous carbon material, the preparation steps are as follows:
[0045] S1, ball milling: 10 parts of glucosamine, 5 parts of geniposide acid, 1.5 parts of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, 1.5 parts of ammonium persulfate, 2 parts of hexamethylenediamine, 3 parts of a mixture of montmorillonite and hydrotalcite in a mass ratio of 1:1 and 30 parts of distilled water are placed in a high-energy ball mill, ball milled at a speed of 100 r / min for 45 min, and then the ball milling is repeated 4 times at a speed of 600 r / min, with a single ball milling time of 30 min, and the mixture is allowed to stand for 45 min in the middle to obtain an intermediate product mixture, which is dried to obtain a solid intermediate product;
[0046] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0047] S3, pickling: The black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water rinse was neutral to obtain a nitrogen-doped biomass-based porous carbon material with a yield of 30%.
[0048] Example 3
[0049] A nitrogen-doped biomass-based porous carbon material, the preparation steps are as follows:
[0050] S1, ball milling: 10 parts of chitosan oligosaccharide, 5 parts of geniposide acid, 1.5 parts of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, 1.5 parts of ammonium persulfate, 2 parts of hexamethylenediamine, 3 parts of a mixture of montmorillonite and hydrotalcite in a mass ratio of 1:1 and 30 parts of distilled water are placed in a high-energy ball mill, ball milled and mixed at a speed of 100 r / min for 45 min, and then ball milled 4 times at a speed of 600 r / min, with a single ball milling time of 30 min, and allowed to stand for 45 min in the middle to obtain an intermediate product mixture, which is dried to obtain a solid intermediate product;
[0051] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0052] S3, pickling: The black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water rinse was neutral to obtain a nitrogen-doped biomass-based porous carbon material with a yield of 31%.
[0053] Example 4
[0054] A nitrogen-doped biomass-based porous carbon material, the preparation steps are as follows:
[0055] S1, ball milling: 10 parts of hydroxypropyl chitosan, 5 parts of geniposide acid, 1.5 parts of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, 1.5 parts of ammonium persulfate, 2 parts of hexamethylenediamine, 3 parts of a mixture of montmorillonite and hydrotalcite in a mass ratio of 1:1 and 30 parts of distilled water are placed in a high-energy ball mill, ball milled at a speed of 100 r / min for 45 min, and then the ball milling is repeated 4 times at a speed of 600 r / min, with a single ball milling time of 30 min, and the intermediate product mixture is allowed to stand for 45 min to obtain an intermediate product mixture, which is dried to obtain a solid intermediate product;
[0056] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0057] S3, pickling: The black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water rinse was neutral to obtain a nitrogen-doped biomass-based porous carbon material with a yield of 32%.
[0058] Example 5
[0059] A nitrogen-doped biomass-based porous carbon material, the preparation steps are as follows:
[0060] S1, ball milling: 10 parts of chitosan, 5 parts of genipin, 1.5 parts of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, 1.5 parts of ammonium persulfate, 2 parts of hexamethylenediamine, 3 parts of a mixture of montmorillonite and hydrotalcite in a mass ratio of 1:1 and 30 parts of distilled water are placed in a high-energy ball mill, ball milled and mixed at a speed of 100 r / min for 45 min, and then the ball milling is repeated 4 times at a speed of 600 r / min, with a single ball milling time of 30 min, and the intermediate product mixture is allowed to stand for 45 min to obtain an intermediate product mixture, which is dried to obtain a solid intermediate product;
[0061] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0062] S3, pickling: The black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water rinse was neutral to obtain a nitrogen-doped biomass-based porous carbon material with a yield of 31%.
[0063] Example 6
[0064] A nitrogen-doped biomass-based porous carbon material, the preparation steps are as follows:
[0065] S1, ball milling: 10 parts of chitosan, 5 parts of geniposide, 1.5 parts of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, 1.5 parts of ammonium persulfate, 2 parts of hexamethylenediamine, 3 parts of a mixture of montmorillonite and hydrotalcite in a mass ratio of 1:1 and 30 parts of distilled water are placed in a high-energy ball mill, ball milled and mixed at a speed of 100 r / min for 45 min, and then ball milled 4 times at a speed of 600 r / min, with a single ball milling time of 30 min, and allowed to stand for 45 min in the middle to obtain an intermediate product mixture, which is dried to obtain a solid intermediate product;
[0066] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0067] S3, pickling: The black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water rinse was neutral to obtain a nitrogen-doped biomass-based porous carbon material with a yield of 28%.
[0068] Example 7
[0069] A nitrogen-doped biomass-based porous carbon material, the preparation steps are as follows:
[0070] S1, ball milling: 10 parts of chitosan, 3 parts of geniposide acid, 1 part of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, 1 part of ammonium persulfate, 1 part of hexamethylenediamine, 2 parts of a mixture of montmorillonite and hydrotalcite in a mass ratio of 1:1 and 20 parts of distilled water are placed in a high-energy ball mill, ball milled at a speed of 100 r / min for 45 min, and then the ball milling is repeated 4 times at a speed of 600 r / min, with a single ball milling time of 30 min, and the intermediate product mixture is allowed to stand for 45 min to obtain an intermediate product mixture, which is dried to obtain a solid intermediate product;
[0071] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0072] S3, pickling: The black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water rinse was neutral to obtain a nitrogen-doped biomass-based porous carbon material with a yield of 23%.
[0073] Example 8
[0074] A nitrogen-doped biomass-based porous carbon material, the preparation steps are as follows:
[0075] S1, ball milling: 10 parts of chitosan, 8 parts of geniposide acid, 2 parts of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, 2 parts of ammonium persulfate, 3 parts of hexamethylenediamine, 4 parts of a mixture of montmorillonite and hydrotalcite in a mass ratio of 1:1 and 50 parts of distilled water are placed in a high-energy ball mill, ball milled and mixed at a speed of 100 r / min for 45 min, and then ball milled 4 times at a speed of 600 r / min, with a single ball milling time of 30 min, and allowed to stand for 45 min in the middle to obtain an intermediate product mixture, which is dried to obtain a solid intermediate product;
[0076] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0077] S3, acid washing: the black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water washing liquid was neutral to obtain the product nitrogen-doped biomass-based porous carbon material with a yield of 27%.
[0078] Example 9
[0079] A nitrogen-doped biomass-based porous carbon material, the preparation steps are as follows:
[0080] S1, ball milling: 10 parts of chitosan, 5 parts of geniposide acid, 1.5 parts of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, 1.5 parts of ammonium persulfate, 2 parts of hexamethylenediamine, 3 parts of a mixture of montmorillonite and hydrotalcite in a mass ratio of 1:0.4 and 30 parts of distilled water are placed in a high-energy ball mill, ball milled and mixed at a speed of 100 r / min for 45 min, and then the ball milling is repeated 4 times at a speed of 600 r / min, the single ball milling time is 30 min, and the intermediate product mixture is allowed to stand for 45 min to obtain an intermediate product mixture, which is dried to obtain a solid intermediate product;
[0081] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0082] S3, acid washing: the black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water washing liquid was neutral to obtain the product nitrogen-doped biomass-based porous carbon material with a yield of 26%.
[0083] Example 10
[0084] A nitrogen-doped biomass-based porous carbon material, the preparation steps are as follows:
[0085] S1, ball milling: 10 parts of chitosan, 5 parts of geniposide acid, 1.5 parts of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, 1.5 parts of ammonium persulfate, 2 parts of hexamethylenediamine, 3 parts of a mixture of montmorillonite and hydrotalcite in a mass ratio of 1:2.7 and 30 parts of distilled water are placed in a high-energy ball mill, ball milled at a speed of 100 r / min for 45 min, and then the ball milling is repeated 4 times at a speed of 600 r / min, with a single ball milling time of 30 min, and the intermediate product mixture is allowed to stand for 45 min to obtain an intermediate product mixture, which is dried to obtain a solid intermediate product;
[0086] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0087] S3, pickling: The black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water rinse was neutral to obtain a nitrogen-doped biomass-based porous carbon material with a yield of 24%.
[0088] Embodiment 11
[0089] A nitrogen-doped biomass-based porous carbon material, the preparation steps are as follows:
[0090] S1, ball milling: 10 parts of chitosan, 5 parts of geniposide acid, 1.5 parts of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, 1.5 parts of ammonium persulfate, 2 parts of hexamethylenediamine, 3 parts of a mixture of montmorillonite and hydrotalcite in a mass ratio of 1:1 and 30 parts of distilled water are placed in a high-energy ball mill, ball milled at a speed of 80 r / min for 60 min, and then ball milled 5 times at a speed of 500 r / min, with a single ball milling time of 40 min, and allowed to stand for 60 min in the middle to obtain an intermediate product mixture, which is dried to obtain a solid intermediate product;
[0091] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0092] S3, pickling: The black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water rinse was neutral to obtain a nitrogen-doped biomass-based porous carbon material with a yield of 30%.
[0093] Example 12
[0094] A nitrogen-doped biomass-based porous carbon material, the preparation steps are as follows:
[0095] S1, ball milling: 10 parts of chitosan, 5 parts of geniposide acid, 1.5 parts of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, 1.5 parts of ammonium persulfate, 2 parts of hexamethylenediamine, 3 parts of a mixture of montmorillonite and hydrotalcite in a mass ratio of 1:1 and 30 parts of distilled water are placed in a high-energy ball mill, ball milled and mixed at a speed of 150r / min for 30min, and then ball milled 3 times at a speed of 800r / min, with a single ball milling time of 20min, and allowed to stand for 30min in the middle to obtain an intermediate product mixture, which is dried to obtain a solid intermediate product;
[0096] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0097] S3, pickling: The black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water rinse was neutral to obtain a nitrogen-doped biomass-based porous carbon material with a yield of 32%.
[0098] Example 13
[0099] A nitrogen-doped biomass-based porous carbon material, the preparation steps are as follows:
[0100] S1, ball milling: 10 parts of chitosan, 5 parts of geniposide acid, 1.5 parts of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, 1.5 parts of ammonium persulfate, 2 parts of hexamethylenediamine, 3 parts of a mixture of montmorillonite and hydrotalcite in a mass ratio of 1:1 and 30 parts of distilled water are placed in a high-energy ball mill, ball milled and mixed at a speed of 100 r / min for 45 min, and then the ball milling is repeated 4 times at a speed of 600 r / min, with a single ball milling time of 30 min, and the intermediate product mixture is allowed to stand for 45 min to obtain an intermediate product mixture, which is dried to obtain a solid intermediate product;
[0101] S2, carbonization: the solid intermediate obtained in S1 was placed in a tube furnace into which an argon atmosphere was introduced at a rate of 10 mL / min, the temperature was raised from room temperature to 800°C at a rate of 2°C / min, the temperature was kept at that temperature for 4 hours, and the temperature was then programmed to decrease to room temperature at a rate of 3°C / min to obtain a black product;
[0102] S3, acid washing: the black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water washing liquid was neutral to obtain the product nitrogen-doped biomass-based porous carbon material with a yield of 29%.
[0103] Embodiment 14
[0104] A nitrogen-doped biomass-based porous carbon material, the preparation steps are as follows:
[0105] S1, ball milling: 10 parts of chitosan, 5 parts of geniposide acid, 1.5 parts of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, 1.5 parts of ammonium persulfate, 2 parts of hexamethylenediamine, 3 parts of a mixture of montmorillonite and hydrotalcite in a mass ratio of 1:1 and 30 parts of distilled water are placed in a high-energy ball mill, ball milled and mixed at a speed of 100 r / min for 45 min, and then the ball milling is repeated 4 times at a speed of 600 r / min, with a single ball milling time of 30 min, and the intermediate product mixture is allowed to stand for 45 min to obtain an intermediate product mixture, which is dried to obtain a solid intermediate product;
[0106] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a helium atmosphere was introduced at a rate of 30 mL / min, the temperature was raised from room temperature to 1000°C at a rate of 3°C / min, the temperature was kept at that temperature for 2 hours, and the temperature was then programmed to decrease to room temperature at a rate of 8°C / min to obtain a black product;
[0107] S3, acid washing: the black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water washing liquid was neutral to obtain the product nitrogen-doped biomass-based porous carbon material with a yield of 27%.
[0108] Comparative Example 1
[0109] A carbon material, the preparation steps are as follows:
[0110] S1, ball milling: 10 parts of chitosan, 5 parts of geniposide acid, 3 parts of a mixture of montmorillonite and hydrotalcite in a mass ratio of 1:1 and 30 parts of distilled water were placed in a high-energy ball mill, ball milled at a speed of 100 r / min for 45 min, and then repeated at a speed of 600 r / min for 4 times, with a single ball milling time of 30 min, and allowed to stand for 45 min in the middle to obtain an intermediate product mixture, which was dried to obtain a solid intermediate product;
[0111] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0112] S3, pickling: The black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water rinse was neutral to obtain a nitrogen-doped biomass-based porous carbon material with a yield of 11%.
[0113] Comparative Example 2
[0114] A carbon material, the preparation steps are as follows:
[0115] S1, ball milling: 10 parts of chitosan, 5 parts of geniposide acid, 1.5 parts of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, 1.5 parts of ammonium persulfate, 3 parts of a mixture of montmorillonite and hydrotalcite in a mass ratio of 1:1 and 30 parts of distilled water were placed in a high-energy ball mill, ball milled at a speed of 100 r / min for 45 min, and then repeated ball milling at a speed of 600 r / min for 4 times, with a single ball milling time of 30 min, and allowed to stand for 45 min in the middle to obtain an intermediate product mixture, which was dried to obtain a solid intermediate product;
[0116] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0117] S3, acid washing: the black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water washing liquid was neutral to obtain the product nitrogen-doped biomass-based porous carbon material with a yield of 14%.
[0118] Comparative Example 3
[0119] A carbon material, the preparation steps are as follows:
[0120] S1, ball milling: 10 parts of chitosan, 5 parts of geniposide acid, 3 parts of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, 2 parts of hexamethylenediamine, 3 parts of a mixture of montmorillonite and hydrotalcite in a mass ratio of 1:1, and 30 parts of distilled water are placed in a high-energy ball mill, ball milled and mixed at a speed of 100 r / min for 45 min, and then the ball milling is repeated 4 times at a speed of 600 r / min, with a single ball milling time of 30 min, and the intermediate product mixture is allowed to stand for 45 min to obtain an intermediate product mixture, which is dried to obtain a solid intermediate product;
[0121] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0122] S3, pickling: The black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water rinse was neutral to obtain a nitrogen-doped biomass-based porous carbon material with a yield of 16%.
[0123] Comparative Example 4
[0124] A carbon material, the preparation steps are as follows:
[0125] S1, ball milling: 10 parts of chitosan, 5 parts of geniposide acid, 3 parts of ammonium persulfate, 2 parts of hexamethylenediamine, 3 parts of a mixture of montmorillonite and hydrotalcite in a mass ratio of 1:1 and 30 parts of distilled water were placed in a high-energy ball mill, ball milled at a speed of 100 r / min for 45 min, and then repeated at a speed of 600 r / min for 4 times, with a single ball milling time of 30 min, and allowed to stand for 45 min in the middle to obtain an intermediate product mixture, which was dried to obtain a solid intermediate product;
[0126] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0127] S3, pickling: The black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water rinse was neutral to obtain a nitrogen-doped biomass-based porous carbon material with a yield of 18%.
[0128] Comparative Example 5
[0129] A carbon material, the preparation steps are as follows:
[0130] S1, ball milling: 10 parts of chitosan, 5 parts of geniposide acid, 1.5 parts of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, 1.5 parts of ammonium persulfate, 2 parts of hexamethylenediamine and 30 parts of distilled water are placed in a high-energy ball mill, ball milled and mixed at a speed of 100 r / min for 45 min, and then the ball milling is repeated 4 times at a speed of 600 r / min, and the single ball milling time is 30 min. The intermediate product mixture is allowed to stand for 45 min to obtain an intermediate product mixture, which is then dried to obtain a solid intermediate product;
[0131] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0132] S3, pickling: The black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water rinse was neutral to obtain a nitrogen-doped biomass-based porous carbon material with a yield of 20%.
[0133] Comparative Example 6
[0134] A carbon material, the preparation steps are as follows:
[0135] S1, ball milling: 10 parts of chitosan, 5 parts of geniposide acid, 1.5 parts of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, 1.5 parts of ammonium persulfate, 2 parts of hexamethylenediamine, 3 parts of montmorillonite and 30 parts of distilled water are placed in a high-energy ball mill, ball milled and mixed at a speed of 100 r / min for 45 min, and then the ball milling is repeated 4 times at a speed of 600 r / min, with a single ball milling time of 30 min, and the intermediate product mixture is allowed to stand for 45 min to obtain an intermediate product mixture, which is then dried to obtain a solid intermediate product;
[0136] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0137] S3, pickling: The black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water rinse was neutral to obtain a nitrogen-doped biomass-based porous carbon material with a yield of 17%.
[0138] Comparative Example 7
[0139] A carbon material, the preparation steps are as follows:
[0140] S1, ball milling: 10 parts of chitosan, 5 parts of geniposide acid, 1.5 parts of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, 1.5 parts of ammonium persulfate, 2 parts of hexamethylenediamine, 3 parts of hydrotalcite and 30 parts of distilled water are placed in a high-energy ball mill, ball milled and mixed at a speed of 100 r / min for 45 min, and then the ball milling is repeated 4 times at a speed of 600 r / min, with a single ball milling time of 30 min, and the intermediate product mixture is allowed to stand for 45 min to obtain an intermediate product mixture, which is then dried to obtain a solid intermediate product;
[0141] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0142] S3, pickling: The black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water rinse was neutral to obtain a nitrogen-doped biomass-based porous carbon material with a yield of 15%.
[0143] Comparative Example 8
[0144] A carbon material, the preparation steps are as follows:
[0145] S1, ball milling: 10 parts of chitosan, 5 parts of geniposide acid, 1.5 parts of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, 1.5 parts of ammonium persulfate, 2 parts of hexamethylenediamine, 3 parts of a mixture of montmorillonite and hydrotalcite in a mass ratio of 1:1, and 30 parts of distilled water were allowed to stand for 300 minutes to obtain an intermediate product mixture, which was dried to obtain a solid intermediate product;
[0146] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0147] S3, acid washing: the black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water washing liquid was neutral to obtain the product nitrogen-doped biomass-based porous carbon material with a yield of 12%.
[0148] Comparative Example 9
[0149] A carbon material, the preparation steps are as follows:
[0150] S1, ball milling: 10 parts of chitosan, 5 parts of geniposide acid, 3 parts of florisil and 30 parts of distilled water were placed in a high-energy ball mill, ball milled at a speed of 100 r / min for 45 min, and then repeated at a speed of 600 r / min for 4 times, with a single ball milling time of 30 min, and allowed to stand for 45 min in the middle to obtain an intermediate product mixture, which was dried to obtain a solid intermediate product;
[0151] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0152] S3, pickling: The black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water rinse was neutral to obtain a nitrogen-doped biomass-based porous carbon material with a yield of 9%.
[0153] Comparative Example 10
[0154] A carbon material, the preparation steps are as follows:
[0155] S1, ball milling: 10 parts of chitosan, 5 parts of geniposide acid, 3 parts of anhydrous borax and 30 parts of distilled water were placed in a high-energy ball mill, and ball milled at a speed of 100 r / min for 45 min, and then repeated at a speed of 600 r / min for 4 times, with a single ball milling time of 30 min, and the intermediate product mixture was allowed to stand for 45 min to obtain an intermediate product mixture, which was dried to obtain a solid intermediate product;
[0156] S2, carbonization: the solid intermediate obtained in S1 was placed in a tubular furnace into which a nitrogen atmosphere was introduced at a rate of 20 mL / min, the temperature was raised from room temperature to 900°C at a rate of 2.5°C / min, the temperature was kept at that temperature for 3 hours, and the temperature was then programmed to decrease to room temperature at a rate of 5°C / min to obtain a black product;
[0157] S3, pickling: The black product obtained in S2 was washed with a 1M hydrochloric acid solution, and then rinsed with distilled water. The acid washing and water washing operations were repeated until the distilled water rinse was neutral to obtain a nitrogen-doped biomass-based porous carbon material with a yield of 10%.
[0158] Test example: Nitrogen adsorption and desorption test
[0159] The nitrogen-doped biomass-based porous carbon materials obtained in Examples 1-14 and Comparative Examples 1-10 were subjected to nitrogen adsorption and desorption tests, and the results are shown in Table 1:
[0160] Table 1 Test results of nitrogen-doped biomass-based porous carbon materials obtained in Examples 1-14 and Comparative Examples 1-10
[0161]
[0162] Effect example: Carbon dioxide adsorption experiment
[0163] Carbon dioxide adsorption experiments were conducted on the nitrogen-doped biomass-based porous carbon materials obtained in Examples 1-14 and Comparative Examples 1-10. The results are shown in Table 2:
[0164] Table 2 Carbon dioxide adsorption of nitrogen-doped biomass-based porous carbon materials obtained in Examples 1-14 and Comparative Examples 1-10
[0165]
[0166] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art may still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A nitrogen-doped biomass-based porous carbon material, characterized in that: The preparation steps are as follows: S1. Ball milling: placing the biomass raw material, the crosslinking agent, 2,2-azobis(2-methylpropylimidazole) dihydrochloride, ammonium persulfate, hexamethylenediamine, a mixture of montmorillonite and hydrotalcite, and distilled water in a high-energy ball mill for ball milling to obtain an intermediate product mixture, which is then dried to obtain a solid intermediate product; S2, carbonization: carbonize the solid intermediate obtained in S1 under a protective gas atmosphere to obtain a black product; S3, pickling: pickling the black product obtained in S2 to obtain a product carbon material; The biomass raw material includes one or more of chitosan, glucosamine, chitosan oligosaccharide and hydroxypropyl chitosan; The cross-linking agent includes one or more of geniposide, geniposide and geniposide; The mass ratio of the biomass raw material, the crosslinking agent, 2,2-azobis(2-methylpropylimidazole) dihydrochloride, ammonium persulfate, hexamethylenediamine, a mixture of montmorillonite and hydrotalcite, and distilled water is 10:3-8:1-2:1-2:1-3:2-4:20-50.
2. The nitrogen-doped biomass-based porous carbon material according to claim 1, characterized in that: The mass ratio of the biomass raw material, the crosslinking agent, 2,2-azobis(2-methylpropylimidazole) dihydrochloride, hexamethylenediamine, a mixture of montmorillonite and hydrotalcite, and distilled water is 10:5:1.5:1.5:2:3:
30.
3. The nitrogen-doped biomass-based porous carbon material according to claim 1, characterized in that: The mass ratio of montmorillonite to hydrotalcite in the montmorillonite and hydrotalcite mixture is 1:0.4-2.
7.
4. The nitrogen-doped biomass-based porous carbon material according to claim 1, characterized in that: The ball milling operation is as follows: ball milling and mixing at a rotation speed of 80-150 r / min for 30-60 min, and then repeating the ball milling at a rotation speed of 500-800 r / min for 3-5 times, with a single ball milling time of 20-40 min, and standing for 30-60 min in between.
5. The nitrogen-doped biomass-based porous carbon material according to claim 1, characterized in that: The protective gas introduction rate is 10-30 mL / min; the protective gas includes one or more of nitrogen, argon and helium.
6. The nitrogen-doped biomass-based porous carbon material according to claim 1, characterized in that: The carbonization operation is as follows: heating from room temperature to 800-1000°C at a rate of 2-3°C / min, keeping the temperature for 2-4 hours, and then cooling to room temperature at a rate of 3-8°C / min.
7. The nitrogen-doped biomass-based porous carbon material according to claim 1, characterized in that: The pickling operation is: washing the product with a hydrochloric acid solution, then rinsing with distilled water, and repeating the operations of pickling and then rinsing with water until the distilled water rinse is neutral.
8. A method for preparing the nitrogen-doped biomass-based porous carbon material as claimed in any one of claims 1 to 7.
9. Use of the nitrogen-doped biomass-based porous carbon material as claimed in any one of claims 1 to 7 in the field of CO2 adsorption.
Citation Information
Patent Citations
Microporous carbon aerogel and preparation method thereof
CN106976864A
Preparation method and application of nitrogen-containing porous carbon material based on polyaspartic acid salt
CN110577206A
A carbon dioxide adsorbent preparation method
CN102688742A
Amine-modified nitrogen-doped carbon material as well as preparation method and application thereof
CN117619349A